1946
DOI: 10.1037/h0060623
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enforced wakefulness upon the growth and the maze-learning performance of white rats.

Abstract: The familiar admonition to "get more sleep" reflects a presumption that loss of sleep is deleterious. This presumption is substantiated by experimental investigations which have shown that prolonged, uninterrupted deprivation of sleep leads, in human beings, to hallucinations and to other evidences of mental disorganization (1,9,13,14,16). Animal subjects have, indeed, been kept awake until they collapsed and died (3,6,10,17).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1959
1959
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…This is surprising in view of the fact that it was demonstrated 50 years ago that, although rats could tolerate prolonged (10-to 18-wk) partial sleep restriction (sleep allowed for only 4 h per day), such loss led to reduced growth and made the rats extremely irritable and reactive (14). We have identified only one study where sleep homeostasis was specifically assessed in animals exposed to a mild chronic sleep restriction protocol (15).…”
mentioning
confidence: 79%
“…This is surprising in view of the fact that it was demonstrated 50 years ago that, although rats could tolerate prolonged (10-to 18-wk) partial sleep restriction (sleep allowed for only 4 h per day), such loss led to reduced growth and made the rats extremely irritable and reactive (14). We have identified only one study where sleep homeostasis was specifically assessed in animals exposed to a mild chronic sleep restriction protocol (15).…”
mentioning
confidence: 79%
“…In fact, the opposite is true. Sleep deprived rats appear to be less fearful and more aggressive (7, 25). In addition, sleep deprivation was shown to reverse stress‐induced behavioural signs of anxiety and depression (26).…”
Section: Discussionmentioning
confidence: 99%
“…Since rats normally sleep approximately 12 h each day (6), we hypothesized that 4 h of sleep would not be sufficient to fully recover from the 20 h of wakefulness. A previous study that applied a similar protocol of restricted sleep in rats showed that the animals survive well, but there was no report on the physiological consequences (7). The rats were allowed to sleep in their home cage the first 4 h of the light phase (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Yet stress is inherent in many commonly used methods for long-term SD in animals. For instance, forced locomotion on a treadmill or in a wheel prevents rest (Licklider and Bunch, 1946;Stefurak et al, 1977), and the platform-over-water method prevents locomotion (Cohen and Dement, 1965). Both these SD methods augment corticosterone release (Murison et al, 1982;Youngblood et al, 1997;Meerlo et al, 2002).…”
Section: Introductionmentioning
confidence: 97%